It's My Time: applying the health belief model to prevent cervical cancer among college-age women. Issue 2 (8th May 2018) - Sundstrom, Beth; Brandt, Heather M.; Gray, Lisa; Young Pierce, Jennifer
Abstract : Purpose: Cervical cancer (CxCa) incidence and mortality remain unacceptably high in South Carolina, USA, presenting an ideal opportunity for intervention. To address this need, Cervical Cancer-Free South Carolina developed an academic-community partnership with researchers and students at a public university to design, implement, and evaluate a theory-based CxCa communication campaign, It's My Time. The paper aims to discuss this issue. Design/methodology/approach: The goal of this campaign was to decrease CxCa by increasing human papillomavirus (HPV) vaccination and appropriate screening. This paper describes the development, implementation, and evaluation of a successful theory-based CxCa prevention communication campaign for college women based on formative audience research and targeted messages delivered to audience segments through new and traditional communication channels. The health belief model (HBM) served as a theoretical framework for the campaign throughout development, implementation, and evaluation. Findings: This campaign demonstrated the effectiveness of the HBM to address CxCa prevention, including HPV vaccine acceptability. The campaign aimed to increase perceptions of susceptibility, which were low, by emphasizing that HPV is a sexually transmitted infection. A community-based grassroots approach to addressing disparities in CxCa prevention increased benefits and decreased barriers. Social media emerged as a particularly appropriate platform to disseminate cues to action. In total, 60 percent of participants who responded to an anonymous web-based survey evaluation indicated that they received the HPV vaccine as a result of campaign messages. Originality/value: This paper offers practical suggestions to campaign planners about building academic-community partnerships to develop theory-based communication campaigns that include conducting formative research, segmenting target audiences, engaging with young people, and incorporating social media.